2013
DOI: 10.1038/aps.2013.27
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and targeting cancer stem cells: therapeutic implications and challenges

Abstract: Cancer stem cells (CSCs) have been identified as rare cell populations in many cancers, including leukemia and solid tumors. Accumulating evidence has suggested that CSCs are capable of self-renewal and differentiation into various types of cancer cells. Aberrant regulation of gene expression and some signaling pathways has been observed in CSCs compared to other tumor cells. CSCs are thought to be responsible for cancer initiation, progression, metastasis, recurrence and drug resistance. The CSC hypothesis ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
403
0
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 539 publications
(427 citation statements)
references
References 99 publications
3
403
0
8
Order By: Relevance
“…[49][50][51] In this study, while we found that RT treatment increased the CSCs in the primary s.c. tumor compared with PBS-treated control, the percentage of ALDH high CSCs decreased significantly after RT plus CSC-DC vaccination from control (»15%) to <3%, which was also significantly less than those after treatment with RT alone (»20%) or with RT plus ALDH low DC vaccination (»12%). These results indicate that CSC-DC vaccine could induce direct targeting of CSCs.…”
Section: Discussionsupporting
confidence: 48%
“…[49][50][51] In this study, while we found that RT treatment increased the CSCs in the primary s.c. tumor compared with PBS-treated control, the percentage of ALDH high CSCs decreased significantly after RT plus CSC-DC vaccination from control (»15%) to <3%, which was also significantly less than those after treatment with RT alone (»20%) or with RT plus ALDH low DC vaccination (»12%). These results indicate that CSC-DC vaccine could induce direct targeting of CSCs.…”
Section: Discussionsupporting
confidence: 48%
“…The signaling pathways utilized by both normal stem cells and CSCs overlap and are based on embryonic signaling pathways which allow self-renewal. Advancement of knowledge in the concept of Cancer Stem Cells and their encouraging results suggest new directions in the treatment of cancer as they are thought to be responsible for tumor initiation, progression, therapy resistance, relapse and metastasis [16]. The well accepted CSC markers of are CD44, CD24, CD133, CD166 and EpCAM and a few more [17] and most of them are also reported in Gall Bladder Cancer.…”
Section: Role Of Cancer Stem Cells In Tumorigenesismentioning
confidence: 99%
“…Several landmark papers evidence dysregulation of signalling pathways in the control of self-renewal and differentiation of hepatic stem cells and include PI3K/ Akt, JAK/STAT, Wnt/β-catenin, hedgehog, Notch, NF-κB and ABC transporters to influence stemness of CSCs. [4,5] Knowledge on these pathways permits the development of molecularly targeted therapies.…”
Section: Jürgen Borlakmentioning
confidence: 99%